The Effect of Giving Warm Compress on Neck Pain in Hypertension Elderly at Simundol Puskesmas Regency Northern Padang Lawas Year 2022 - Kristina (Institute of Computer Science (IOCS), 2022)
Health is one of the most important human needs, because humans have the right to have health. In fact, not everyone can have optimal health due to environmental, socio-economic, lifestyle, habits and the surrounding environment. Hypertension is a disease that is often found in health services. Signs and symptoms that accompany hypertension such as heart palpitations, difficulty breathing after working hard, fatigue, irritability, neck tension, likes to sleep and so on. The neck feels tense or neck pain is caused by increased pressure on the walls of the blood vessels in the neck area where the blood vessels carry blood to the area to the brain so that when there is an increase in vascular pressure to the brain it results in pain in the nape area. This study aims to identify the effect of giving warm compresses to neck pain in elderly hypertensives at the Simundol Health Center, Kab. North Padang Lawas in 2022. This research is a research using quantitative methods with the type of one group pretest posttest. The number of respondents in this study were 26 respondents. The sampling technique in this study was to use purposive sampling. The results of the study were that before applying warm compresses, 16 respondents experienced severe pain and 10 respondents experienced moderate pain, whereas after warm compresses, 14 respondents experienced mild pain and 12 respondents experienced moderate pain. The conclusion in this study is that there is a significant effect of giving warm compresses to neck pain in elderly hypertensives at the Simundol Health Center, Kab. North Padang Lawas in 2022. The suggestion in this study is that the Simundol Health Center in Kab. North Padang Lawas can improve socialization of the treatment of neck pain in elderly hypertensives by giving warm compresses.